Birth of periodic Micro/Nano structures on 316L stainless steel surface following femtosecond laser irradiation; single and multi scanning study. (August 2018) - Razi, Sepehr; Varlamova, Olga; Reif, Juergen; Bestehorn, Michael; Varlamov, Sergej; Mollabashi, Mahmoud; Madanipour, Khosro; Ratzke, Markus
Highlights: LIPSS are created on 316L-SS surface by femtosecond laser irradiation. Multi scanning results in structures with shorter periodicity and more regularity. Structures periodicity decreases with increasing the irradiation dose. Surface roughness increases by raising the irradiation dose. Results support the self organization theory of structure creation. Abstract: Formation of coherent laser induced periodic surface structures (LIPSS) on stainless steel type 316L by 100 fs laser pulses at 800 nm wavelength is investigated. Specifically focusing on the large area treatment, effect of the irradiation dose (fluence × pulse number) on the uniformity of the morphology, orientation of the ripples respect to the laser polarization and their periodicity is studied systematically. Controlling the pulse number via varying the scanning speed, the difference between irradiating one particular dose in single scan with its irradiation in separate steps is inspected. Results clearly point out that not only the irradiation dose but also the irradiation way and the time delay between the pulse trains might have a significant effect on the final outcomes. It is discussed in detail that the experimental observations are supporting the model of self-organized structure formation due to irradiation induced instability.